AN ANALYSIS OF INFORMATION SEARCH AND RETRIEVAL TECHNIQUES - Otilia Cangea (Romanian Journal of Petroleum & Gas Technology, 2023)
The informational growth dramatically changed the standard form of publication, access, and use of scientific information. Due to Internet, scientific publications migrated from the traditional to a digital configuration. Common users, as well as highly trained professionals from various fields, aim to retrieve information in the shortest possible time, but in the context of an unprecedented growth of data volume, big difficulties occur in finding and accessing the available information, resulting in stress and important delays in decision making. Therefore, training courses in information culture are organized in university libraries, particularly for a superior efficiency of scientific data bases usage. The paper presents an introduction to the architecture of a retrieval information system and a study of the most popular search engines and of the indexing process. Hereinafter, a Page Rank algorithm implementation is performed and a comparative study relative to different search engines is conducted, emphasizing the specific advantages and disadvantages.